EVENTS AS A MEANS OF DISCIPLINE (World Bulletin of Social Sciences, 2023)
The article highlights the importance of using events to shape the spiritual qualities of elementary school students. Their role in human perfection is based. The content of methods that can be used within the age characteristics of students is interrupted.
Keywords: event; writer; prophet; upbringing